Factors controlling recent diatom assemblages across a steep local nutrient gradient in central-eastern Finland - Mira Tammelin; Tommi Kauppila; Matias Viitasalo (Springer International Publishing, 2025)
The Iisalmi Route, a chain of lakes in central-eastern Finland, is more eutrophic than its surroundings. We used multivariate analyses to study the influence of selected environmental factors (water quality, basin characteristics, and subcatchment surficial geology) on the recent diatom assemblages across this steep local nutrient gradient. In addition to the spatial analysis of surface sediment diatom assemblages from 51 sampling sites (48 lakes), temporal changes in the total phosphorus (TP) concentrations of one Iisalmi Route lake (Lake Kirmanjärvi) were analyzed using weighted averaging partial least squares regression and 27 fossil diatom samples. Both TP and electrical conductivity (EC) showed statistically significant independent signals in the modern diatom data. The TP gradient was related to till grain size variation suggesting that geological factors affect the spatial TP variation directly or indirectly through differences in land use. Based on the temporal study, the direct effect of geology is most likely behind the steep nutrient gradient in the area because Lake Kirmanjärvi was found to be naturally eutrophic. EC, on the other hand, seems related to anthropogenic disturbance. Our study highlights the importance of taking the local geology into account when assessing past or present water quality or planning for lake management.